Pemodelan Pengaruh Vaksinasi Terhadap Penyebaran Demam Berdarah Dengue (DBD) - Utami, Nita Putri (UIN Imam Bonjol Padang, 2022)
Many people ignore the pain that they are suffering from. This is due to the lack of understanding of the patient about the disease he is suffering from. One type of infectious disease that is often encountered in the community is Dengue Hemorrhagic Fever (DHF). DHF is caused by dengue virus infection. The purpose of this study is to establish a mathematical model to determine the effect of vaccination on the spread of DHF. The method used is by using the Equilibrium Point with SIR. The effect of vaccination on the spread of DHF is fully determined by the basic reproduction number (R_0) is R0=(Î²Î¼(Î¼+Ïƒ)+Î¸Î±Î¼N)/(Î¼+Î³)(Î¼+Î±)(Î¼+Ïƒ) . When R_0<1, the disease-free fixed point E0 will be asymptotically stable which means that the disease will not spread in the population or in other words, the disease will eventually disappear from the population within a year. long time. When R_0>1, the endemic point of Ee will be asymptotically stable which means that the disease will persist and spread in the population. In order for dengue hemorrhagic fever (DHF) to be prevented or eliminated for a long time, we need to reduce the basic reproduction number by increasing the chances of susceptible individuals being vaccinated.